Documenta 14: Daybook. - Parpa, Elena; Latimer, Quinn; Szymczyk, Adam; Szewczyk, Monika; Folkerts, Hendrik; Deliss, Clémentine; Preciado, Paul B.; Trevor, Tom; Januskeviciute, Virginija; Haidu, Rachel; Serban, Alina; Dziewanska, Marta; et al. (München : Prestel Verlag, 2017)
Abounaddara ; Akinbiyi, Akinbode ; Aladag, Nevin ; Anesiadou, Danai ; Angelidakis, Andreas ; Antonas, Aristide ; Araeen, Rasheed ; Ariuntugs Tserenpil ; Auder, Michel ; Bachzetsis, Alexandra ; Baghramian, Nairy ; Baloji, Sammy ; Belmore, Rebecca ; Beqiri Sokol ; Bernat, Roger ; Bidjocka, Bill ; Birrell, Ross ; Braila, Pavel ; Bratescu, Greta ; Cahn, Miriam ; Celmins, Vija ; Cennetoglu, Banu ; Charalambous, Panos ; Chopra, Nikhil ; Ciudad Abierta ; Daucikova, Anna/Anca ; Davey, Moyra ; Davids, Yael ; Denes, Agnes ; Diawara, Mantha ; Dick, Beau ; Eichhorn, Maria ; Eijkelboom, Hans ; Ely, Bonita ; Eshetu, Theo ; Fofana, Aboukar ; Friedl, Peter ; Fofana, Aboubakar ; Galindo, Guillermo ; Galindo, Regina José ; Gbaguidi, Pélagie ; Georgiou, Apostolos ; Gill, Gauri ; Gioti, Marina ; Gonzaelez, Beatriz ; Godron, Douglas ; Haacke, Hans ; Hadzinikolaou, Constantinos ; Haiduk, Irena ; Haloi, Ganesh ; Halprin, Anna ; Harding, Dale ; Harding, david ; Hassabi , Maria ; Hila, Edi ; Hiller, Susan ; Howa K ; Holzapfel, Olaf ; Hookey, Gordon ; Iqhiya, Ivekovic, Sanja ; Kanwar, Amar ; Karmakar, Romuald ; Kassapis, Andreas Ragnar ; Kettly, Noel ; Khalili, Bouchra ; Khvay Samnang ; Knorr, Daniel ; Ladik, Katalin ; LalaRukh ; Lamelas, David ; Lowe, Rick ; Lucier, Alvin ; Mahama, Ibrahim ; Mari, Narimane ; Mata Aho Collective ; Mattin ; Mekas, jonas ; Melitopoulos, Angela ; Menard, Phia ; Meredith-Vula,Lla ; Minke, Gernot ; Minujin, Marta ; Mohaiemen, Naeem ; Nango, Joar ; Nashashibi, Rosalind ; Negros Tou Moria ; Nkanga, Otobong ; Nomin Bold ; Ogboh, Emeka ; Oguibe, Olu ; Oldendorf, Rainer ; Oliveros, Pauline ; Orellana Mejia, Joaquin ; Papoulias, Christos ; Patterson, Benjamin ; Peterman, Dan ; Plessas, Angelo ; Pohio, Nathan ; Pope, L. ; Postcommodity ; Prinz Gholam ; Rose, tracey ; Rosen, Roee ; Rungjang, Arin ; Russell, Ben ; Sagri, Georgia ; Sara, maret anne ; Scheirl, Ashley Hans ; Schutter, david ; Seskus, Algirdas ; Sheikh, Nilima ; Shibli, Ahlam ; Solh, Mounira Al
Documenta 14, Athene, 8 april, Kassel, 17 september
boek